Symptomatic dry eye disease (DED) in cohort of contact lens wearers in Jordan - Wissam Ghach; May M. Bakkar; Mona Aridi; Mohammad A. Alebrahim (PLoS ONE, 2025)
Understanding the symptomatic dry eye disease (DED) and its associated risk factors among contact lens wearers is crucial for clinicians to tailor effective interventions, enhance patient care, and prevent contact lens dropout. This study investigated symptomatic DED and its associated risk factors among a sample of contact lens wearers in Jordan. This cross-sectional study assessed symptomatic DED in a cohort of contact lens wearers in Jordan using an online survey distributed across various social media platforms. A total of 301 participants completed the survey, which included demographic and contact lens profile questions and the Arabic version of the Ocular Surface Disease Index (ARB-OSDI) questionnaire. Statistical analyses explored the associations between OSDI scores, demographics, symptoms, visual-related functions affected by dryness, and triggers of dryness. Among the study population, 77.1% were females, 48.2% were aged 18–24 years old, and 24.87% were soft contact lens wearers. The mean OSDI score was 22.9 ± 17, with 70% showing mild-to-severe dry symptoms and 25% showing severe symptomatic DED. The ANOVA revealed a significant association between symptomatic DED, wearing face masks, longer contact lens age, and poor cleaning habits. The use of lubricant eye drops significantly reduced symptomatic DED with a mean OSDI score of 8.79. The most prevalent dryness symptoms were pain and blurred vision, affecting reading and TV watching in 50% of the population. Wind and air conditioning were the most common environmental triggers, reported by 67.8% and 66.4% of participants, respectively. A high proportion of symptomatic DED was reported in this study population. Wearing face masks, a longer contact lens age, and poor contact lens hygiene were correlated with exaggerated DED symptoms. Conversely, the use of lubricated eye drops reduces the symptoms of DED.